Experimental study of cell integrated heat pipe cooling with a lithium-ion cell emulator. (1st December 2022) - Kleiner, Jan; Lambauer, Florian; Singh, Randeep; Komsiyska, Lidiya; Hinterberger, Michael; Endisch, Christian
Abstract: Novel switchable cells challenge conventional thermal management approaches in battery electric vehicles. The study introduces a novel hybrid cooling approach based on liquid bottom cooling and cell integrated heat pipes. For the experimental investigation a thermal cell emulator is developed and the environmental conditions of a cell in an automotive battery system are reproduced. The validation of the cell emulator reveals almost similar behavior compared to a real prismatic 25 Ah cell with additional access to the internal temperature distribution. Thus, a flexible research tool is introduced for thermal investigations of lithium-ion cells. The subsequent investigation of the cell integrated heat pipes is performed for a switchable cell as an essential part of novel intelligent battery systems. As a result of the experimental investigation a reduction of the core temperature of 2 K during 3C cycling is found using integrated heat pipes. Furthermore, in a case study for fast charging the heat pipes enable consistent temperatures within the cell core, while the charging time is decreased by 12%. Highlights: Cell integrated heat pipe cooling concept for an automotive lithium-ion cell. Investigation of a prototype switchable cell for intelligent battery systems. Setup with thermal imaging camera and electric vehicle boundary conditions. Influence of heat pipe positioning on the cell internal temperature distribution. Electro-thermal cell emulator as a versatile tool for detailed investigations.